2016
DOI: 10.5194/isprsarchives-xli-b1-917-2016
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Forest and Open Area Effects on Snow Accumulation by Unmanned Aerial Vehicle Photogrammetry

Abstract: ABSTRACT:Airborne digital photogrammetry is undergoing a renaissance. The availability of low-cost Unmanned Aerial Vehicle (UAV) platforms well adopted for digital photography and progress in software development now gives rise to apply this technique to different areas of research. Especially in determining snow depth spatial distributions, where repetitive mapping of cryosphere dynamics is crucial. Here, we introduce UAV-based digital photogrammetry as a rapid and robust approach for evaluating snow accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In addition, airborne laser scanning (ALS) and terrestrial laser scanning (TLS) technologies have been applied as the preferred methods to obtain HS data [3,[26][27][28][29][30][31][32][33]. Moreover, tachymetry [28], ground-penetrating radar (GPR) [34,35], and time-lapse photography [36,37] have been used.The use of unmanned aerial system (UAS) technology in snow and avalanche studies has been recently reported in the literature [10,19,33,35,[38][39][40][41][42][43][44]. While the first studies on the use of a UAS in HS mapping investigated its potential and limitations by using manual HS probing for accuracy assessment, more recent studies have used time series of a UAS and compared it with other techniques, such as airborne sensors, including the ADS100 [45], TLS [33,44], and tri-stereoscopic Pléiades satellite images [46].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, airborne laser scanning (ALS) and terrestrial laser scanning (TLS) technologies have been applied as the preferred methods to obtain HS data [3,[26][27][28][29][30][31][32][33]. Moreover, tachymetry [28], ground-penetrating radar (GPR) [34,35], and time-lapse photography [36,37] have been used.The use of unmanned aerial system (UAS) technology in snow and avalanche studies has been recently reported in the literature [10,19,33,35,[38][39][40][41][42][43][44]. While the first studies on the use of a UAS in HS mapping investigated its potential and limitations by using manual HS probing for accuracy assessment, more recent studies have used time series of a UAS and compared it with other techniques, such as airborne sensors, including the ADS100 [45], TLS [33,44], and tri-stereoscopic Pléiades satellite images [46].…”
mentioning
confidence: 99%
“…The use of unmanned aerial system (UAS) technology in snow and avalanche studies has been recently reported in the literature [10,19,33,35,[38][39][40][41][42][43][44]. While the first studies on the use of a UAS in HS mapping investigated its potential and limitations by using manual HS probing for accuracy assessment, more recent studies have used time series of a UAS and compared it with other techniques, such as airborne sensors, including the ADS100 [45], TLS [33,44], and tri-stereoscopic Pléiades satellite images [46].…”
mentioning
confidence: 99%
“…Three DoDs were created ( Figure 5 d and Figure 6 e,f ) based on standard photogrammetric procedure Usually, by subtracting the snow-free DSMs from the snow-covered DSMs, the snow depth values appeared negative in the maps, which were classified as outliers but not masked out, and depicted as zero values in the maps, for readability. This discrepancy has already been noted during photogrammetric surveys [ 27 , 28 , 40 ] and can be attributed to the effect of compressible vegetation and instrumental precision [ 28 , 66 ].…”
Section: Resultsmentioning
confidence: 92%
“…Besides manual sampling design as used in this study a lot of promising results have been also reported using remote sensing approaches such as the use of unmanned aerial systems (UAV) (Lendzioch et al 2016;Nolan et al 2015), aerial or terrestrial laser scanning (Bühler et al 2015;Grünewald et al 2013;Revuelto et al 2016) and MODIS satellite data (Duchacek 2014;He et al 2014;Krajčí et al 2016). A camera placed on UAV platform was tested to monitor the snow depth characteristics in our study area, more specifically in the plot D with mixed vegetation (Lendzioch et al 2016).…”
Section: Snow Sampling Designmentioning
confidence: 98%